Sakarya Zonunun Orta Kesiminde Yer Alan Jura Öncesine Ait Temelin Özellikleri Ve Kökeninin Belirlenmesi - Egi, Ali Yetkin (Avrasya Yerbilimleri Enstitüsü, 2020)
Çalışma bölgesi Sakarya zonunun doğu kısmında ve Doğu Pontidlerin batısında yer almaktadır. Bölgenin jeolojisi özet olarak Jura yaşlı ve Neo-Tetis Okyanusu’nun güney pasif kıta kenarını oluşturan çökeller ve onun altındaki temel birimler olarak ifade edilebilir. Erken Jura transgresyonu Paleo-Tetis Okyanusu’nun kapandığı, Gondwana-Kıtası temel birimleri üzerinde gelişmiştir. Temel metamorfikler Tokat masifi fillat, şist, metabazit ve bunların içerisinde yer alan mermer mercekleri ile temsil edilmektedir. Yeşilırmak metamorfitlerinin içerisine faylı şekilde magmatik kütleler yerleşmiştir ve sonrasında da hep beraber bir metamorfizmaya uğramışlardır. Temeli temsil eden bu kayaçlar Alt Jura yaşlı karbonat ve kırıntılı birimlerince uyumsuzlukla örtülmektedir. Üst Kretase’de bölge derin denizel çökellerle temsil edilir. Paleosen dönemi çökelmenin görülmediği bir dönemdir. Lütesiyen ve Neojen birimleri daha yaşlı kayaları (Eosen karasal çökelleri, Kretase ve Jura denizel birimleri ve Jura öncesi temeli) uyumsuzlukla üzerlemektedir. Metamorfik istife stratigrafik ve paleontolojik verilere göre Pre-Silüryen-Silüryen (Alp, 1972) ve Triyas (Çapkınoğlu, 1998) yaşı verilmiş olsa da atfedilen bu yaşlar tartışmalıdır. Ayrıca birçok çalışmada bölgede iki ayrı temel tarif edilmiş ve bunlar arasında da farklı jeolojik ilişkiler belirtilmiştir. Bu çalışma ile bölgede jeolojik haritalama çalışmaları yapılarak temelde yer alan metamorfiklerin özellikleri ve bir birileri ile olan ilişkileri belirlenmiştir. Bu amaçla birimlerden yapısal ölçümler alınıp, petrografi çalışmaları ile birlikte kökenlerine dair veriler elde edilmiştir. Çalışma alanı içerisinde Jura öncesi temel Triyas yaşlı iki birimle temsil edilmektedir. Bunlardan ilki Triyas yaşlı gabrolarca kesilen (Eyüboğlu ve diğ., 2015) Yeşilırmak metamorfitleridir. Birim iyi yapraklanmalı ve yeşilşist fasiyesinde metamorfizmaya uğramış fillat-metabazitlerden oluşmaktadır. İkinci temel ise bu birimin üzerinde yer alan Karasenir formasyonudur. Bu birim çeşitli karbonat blokları içeren düşük metamorfizmalı (ankimetamorfik) bir istiftir. Her ne kadar bu birim Yeşilırmak metamorfitlerine bindiriyor olarak gösterilse de böyle bir ilişki arazide gözlenememiştir. Bu birim Yeşilırmak metamorfitleri üzerinde geçişli olarak gözlenmektedir. Triyas yaşında (erken?) olduğu düşünülen bu temel batı Sakarya temelinde yer alan Karakaya birliğinin eşleniği olarak atfedilmiştir.

The study area is located in the eastern part of the Sakarya zone and in the west of Eastern Pontides. The geology of the region can be summarized as the Jurassic sediments forming the southern passive continental margin of the Neo-Tethyan Ocean and the underlying units. This early Jurassic transgression developed on the pieces of the Gondwana-Landattached during the closure of the the Paleo-Tethyan Ocean. Basement metamorphics The Tokat massif is represented by phyllites, schists, metabasites, marble intersection and marble lenses. These metamorphic rocks contained gabbro block and then metamorphosed together. These rocks are unconformably overlain by Lower Jurassic carbonate and clastic units in shallow marine environment. Upper Cretaceous is represented by deep marine sediments in the region. Paleocene is a period in which no sedimentation is observed. The Lutetian and Neogene units unconformably overlie the older rocks. According to the stratigraphic and paleontological data of the metamorphic sequence, Pre-Silurian-Silurian (Alp, 1972 and Tüysüz, 1996) and Triassic (Çapkınoğlu, 1998) ages are assigned, but these ages are controversial. In addition, different basement rocks and geological relationships between them have been described. In this study, with the aim of mapping studies, determine structural component, geological features of the basement units and the relationship between them have been defined. For the purpose outlined here, structural measurements have been obtained and petrographic studies carried out be able to lighten provenance of the basement units expose in the study area. The pre-Jurassic basement of the region are represented by two units. One of them is Yeşilırmak Metamorphics that contain the Triassic magmatic blocks or cutting by Triassic gabbro (Eyüboğlu et al. 2015). The unit is represented by well foliated schists and phylittes metamorphosed under amphibolite facies. The second one is overlaying Karasenir formation that has several limestone blocks and reveals very low degree metamorphism. The relationship between these units has been described as a thrust fault, but any sign of this fault could be observed in the field studies. Instead, Karasenir formation has transitional contact with underlying Yeşilırmak Metamorphics. These basement units are assigned to Triassic (early?) in this study and regarded as the equivalent of the Karakaya complex that is defined in the western Sakarya zone. In this study, although there are some agreed with old studies, different opinions have been proposed in certain aspects. According to some of the previous studies, the age of Karasenir formation is Silurian however Çapkınoğlu (1998), added Karasenir formation into the upper level of Karakaya complex and determined the age of Karasenir formation as Triassic. Thrust fault cannot be observed between Yeşilırmak and Karasenir formations, and also metamorphism level of Yeşilırmak formation is bigger than the metamorphism level of Karasenir formation. According to this thesis, the relationship between Karakaya and Yeşilırmak formations is stratigraphically conformable. Zircon age data and hafnium isotope data can be helpful to solve this problem. Last some studies (Topuz et al., 2018) showed that Karakaya complex has Permian ophiolitic rocks. It is also known that the stacks forming the Karakaya complex evolved in the subduction zone. Study area is on the boundary of Karakaya and NeoTethyan ocean. Thus, detrital zircon age data can offer a solution to the existing discussions by providing information about the direction of subduction. Geochronology researches show two different age distributions due to the fact that Laurentia and Gondwana have different geological histories and evolution. Tectonic events are associated with age data to be obtained. Accordingly, north-trending and south-trending subductions will give two different age distributions. Thus, the direction of the plunging plate and the subduction can be determined. Ezinepazarı-Sungurlu Fault cut the study area from the middle, and created a valley. The northern side of the valley consists of the upper level of Yeşilırmak formation, marble intermediate level, Karasenir formation and Jurassic shallow marine sediments in spite of the fact that southern side of the valley consists of the lower and middle level of Yeşilırmak formation, magmatic blocks, marble lenses and Cretaceous deep marine sediments. Lower and Middle Triassic - Cretaceous period is remarkable. According to this study, extensional tectonic period led to the formation of horst-graben belt. In Jurassic, shallow marine sediments were deposited in grabens while horsts were exposed to erosion. Eroded units from horst areas rising in the south should have been moved northward into the basin as olistoliths, in case of occurrence of the Bilecik limestones as blocks in the Amasya region (in the north) as claimed. Possibly the Ezinepazarı-Sungurlu fault was formed in the weakness plane of a normal fault that occurred during the extensional period between the LowerMiddle Triassic - Cretaceous period. The north side of the valley and south side of the valley must be formed in the same basin but different locations. Opinions of Alp (1972) and Tüysüz (1996) might be approved due to the fact that measurements of Bilecik limestone have highly different density diagrams from the measurements of older formations. Adequate amount of measurements could not be taken especially from Eocene units. E-W directional compression seems to the cause of deformation in Eocene units however, the compression is perpendicular to the direction of compression N-S required for the formation of the E-W directional suture. For this reason, the data set should be increased in a way that does not allow discussion. The reconstruction of deformations after Eocene will provide a better understanding of the deformations of previous units. Some of the paleomagnetic researches (i.e. Meijers et al., 2010) claim that Anadolides - Torides block and Pontides closure movement caused clockwise rotation in east side of Çankırı basin since Campanian - Maastrichtian age. According to this argument, the compression after Eocene should be in the direction of NE to SW instead of W-E. Besides, direction of the compression before Eocene should be WNW-ESE instead of N-S. The post-Eocene rotation of the region requires more detailed investigation to stand behind of the argument. All of these opinions and facts show that the study area has much more complex history and important geological data. Detailed study can explain the closure of Karakaya complex and can help to understand the relationship between Karakaya complex, Sakarya zone with Pontides. Especially, zircon dating method is very helpful to enlighten the pre-Jurrasic period.
Determination of the Features and Origin of the Pre-Jurassic Basement in Middle Part of the Sakarya Zone
Thesis (M.Sc.) -- İstanbul Technical University, Eurasia Institute of Earth Sciences, Yüksek Lisans
Tez (eng) -- İstanbul Teknik Üniversitesi, Avrasya Yer Bilimleri Enstitüsü, Yüksek Lisans
Keywords: Jeoloji; Sakarya; Stratigrafik; Geology; Sakarya; Stratigraphic